Catalyst free single-step fabrication of SnO2/ZnO core–shell nanostructures - Tharsika, T.; Haseeb, A.S. Md. Abdul; Akbar, S.A.; Sabri, M.F.M. (Elsevier, 2014)
Facile catalyst-free synthesis of SnO2/ZnO core–shell nanowires and hierarchical nanostructures grown via a one-step carbon assisted thermal evaporation method under ambient pressure is reported. A white wool-like mass forms at the side and on top of a quartz boat during the process that was analyzed by field emission scanning electron microscopy (FESEM). X-ray diffraction patterns exhibit that the as-synthesized SnO2/ZnO nanostructures consist of single phase of ZnO and SnO2. Transmission electron microscopy (TEM) suggests that the wool-like mass contains core–shell type SnO2/ZnO nanowires as well as hierarchical nanostructures. In the core–shell nanowires, SnO2 forms the core, while ZnO is the shell. In the hierarchical nanostructures, hexagonal shaped ZnO branches grow on the ZnO shell layer at long growth duration. Both types of nanostructures formed in the quartz boat are suggested to grow by the vapor–solid (VS) mechanism. Structural characteristics of the nanostructures are discussed. These nanostructures may have potential applications in chemical gas sensors and photovoltaic devices.